Relevant Role of Fibronectin-Binding Proteins in Staphylococcus aureus Biofilm-Associated Foreign-Body Infections - Vergara-Irigaray, Marta; Valle, Jaione; Merino, Nekane; Latasa, Cristina; Garcia, Begona; Ruiz de los Mozos, Igor; Solano, Cristina; Toledo-Arana, Alejandro; Penadés, José R.; Lasa, Inigo (2017)
Staphylococcus aureus can establish chronic infections on implanted medical devices due to its capacity to form biofilms. Analysis of the factors that assemble cells into a biofilm has revealed the occurrence of strains that produce either a polysaccharide intercellular adhesin/poly-N-acetylglucosamine (PIA/PNAG) exopolysaccharide- or a protein-dependent biofilm. Examination of the influence of matrix nature on the biofilm capacities of embedded bacteria has remained elusive, because a natural strain that readily converts between a polysaccharide- and a protein-based biofilm has not been studied. Here, we have investigated the clinical methicillin (meticillin)-resistant Staphylococcus aureus strain 132, which is able to alternate between a proteinaceous and an exopolysaccharidic biofilm matrix, depending on environmental conditions. Systematic disruption of each member of the LPXTG surface protein family identified fibronectin-binding proteins (FnBPs) as components of a proteinaceous biofilm formed in Trypticase soy broth-glucose, whereas a PIA/PNAG-dependent biofilm was produced under osmotic stress conditions. The induction of FnBP levels due to a spontaneous agr deficiency present in strain 132 and the activation of a LexA-dependent SOS response or FnBP overexpression from a multicopy plasmid enhanced biofilm development, suggesting a direct relationship between the FnBP levels and the strength of the multicellular phenotype. Scanning electron microscopy revealed that cells growing in the FnBP-mediated biofilm formed highly dense aggregates without any detectable extracellular matrix, whereas cells in a PIA/PNAG-dependent biofilm were embedded in an abundant extracellular material. Finally, studies of the contribution of each type of biofilm matrix to subcutaneous catheter colonization revealed that an FnBP mutant displayed a significantly lower capacity to develop biofilm on implanted catheters than the isogenic PIA/PNAG-deficient mutant.